Galectin-3 facilitates cell-to-cell HIV-1 transmission by altering the composition of membrane lipid rafts in CD4 T cells. (5th June 2022) - Wang, Sheng-Fan; Hung, Yu-Hsien; Tsao, Ching-Han; Chiang, Cho-Ying; Teoh, Pak-Guan; Chiang, Meng-Lin; Lin, Wei-Han; Hsu, Daniel K; Jan, Hau-Ming; Lin, Hsiu-Chu; Lin, Chun-Hung; Liu, Fu-Tong; et al.
Abstract: Galectin-3 (GAL3) is a β-galactoside-binding lectin expressed in CD4 T cells infected with human immunodeficiency virus-1 (HIV-1). GAL3 promotes HIV-1 budding by associating with ALIX and Gag p6. GAL3 has been shown to localize in membrane lipid rafts in dendritic cells and positively regulate cell migration. HIV-1 spreads between T cells by forming supramolecular structures (virological synapses [VSs]), whose integrity depends on lipid rafts. Here, we addressed the potential role of GAL3 in cell-to-cell transmission of HIV-1 in CD4 T cells. GAL3 expressed in donor cells was more important for facilitating HIV-1 cell-to-cell transfer than GAL3 expressed in target cells. GAL3 was found to be co-transferred with Gag from HIV-1-positive donor to HIV-1-negative target T cells. HIV-1 infection induced translocation of GAL3 together with Gag to the cell–cell interfaces and colocalize with GM1, where GAL3 facilitated VS formation. GAL3 regulated the coordinated transfer of Gag and flotillin-1 into plasma membrane fractions. Finally, depletion of GAL3 reduced the cholesterol levels in membrane lipid rafts in CD4 T cells. These findings provide evidence that endogenous GAL3 stimulates lipid raft components and facilitates intercellular HIV-1 transfer among CD4 T cells, offering another pathway by which GAL3 regulates HIV-1 infection. These findings may inform the treatment of HIV-1 infection based on targeting GAL3 to modulate lipid rafts.